Optical absorption and diffusion of iron in ZnS single crystals - Nitsuk, Yu.A.; Vaksman, Yu.F.; Yatsun, V.V.; Purtov, Yu.N. (Functional Materials, 2012)
ZnS:Fe single crystals obtained by diffusion doping were investigated. Spectra of optical density in the range of energies 0.4—3.8 eV were obtained. The concentration of iron in the studied crystals was determined using a magnitude of the shift of the absorption edge. Optical transitions determining the impurity absorption spectrum of ZnS:Fe single crystals were identified. The diffusion profile of Fe impurity was determined by measuring the relative optical density of the crystals in the visible spectral region. The diffusivities of Fe in ZnS crystals in the temperature range of 1220—1320 K were calculated for the first time. At 1270 K the diffusivity of Fe is 2⁻¹⁰ cm²/s.